Viabilidade econômica do uso do biogás proveniente da suinocultura em substituição a fontes externas de energia - Dias, Maria Isabel Alencar; Colen, Fernando; Fernandes, Luiz Arnaldo; Souza, Rogério Marcos de; Bueno, Osmar de Carvalho [UNESP] (EIA Energy in Agriculture, 2013)
The swine culture potentially generates waste with high organic load and pollutants, being responsible for the spread of pathogens, contamination of rivers, groundwater and soils, besides it produces foul odors and emit greenhouse gases. However, the high amount of organic matter, which expresses the amount of pollutant load, reflects the energetic potential of these wastes used as raw material in biogas generation through technology of digesters. The properly use of theses digesters provides the production of clean energy and promotes the conservation of the environment. The economic viability of the implantation of an Indian model digester on a small swine farm was verified based on the value from initial investments of deployment, maintenance costs, depreciation, and on the interest and revenues arising from the system. Besides, the amount of biogas produced daily and the average consumption of biogas by the most common used devices such as refrigerator, stove, water heater, and generator of electricity was calculated.. For a backdrop of 10 years, the results of economic indicators NPV of BRL 57,598.95, IRR of 48.38%, Simple Payback of 2.06 years, and Discounted Payback of 2.3 years, demonstrated a favorable outlook for the use of this technology, with the possibility to generate economic, social and environmental benefits.

A suinocultura é uma atividade potencialmente geradora de dejetos, com elevada carga orgânica, altamente poluente, sendo responsável pela disseminação de patógenos, pela contaminação de rios, de lençóis subterrâneos e de solos, além de produzir odores desagradáveis e emitir gases de efeito estufa. No entanto, o elevado valor de matéria orgânica, que expressa a carga poluidora, reflete o potencial energético desses dejetos utilizados como matéria-prima na geração de biogás, por meio da tecnologia dos biodigestores, que, quando bem empregada, proporciona a produção de energia limpa e promove a conservação do meio ambiente. Por meio do valor dos investimentos iniciais de implantação de um biodigestor, dos custos de manutenção, da depreciação, dos juros e receitas oriundas do sistema, e, conhecendo a quantidade de biogás produzida diariamente e o consumo médio de biogás pelos aparelhos mais comumente utilizados, como geladeira, fogão, aquecedor de água e grupo gerador de energia elétrica, verificou-se a viabilidade econômica da implantação de um biodigestor modelo indiano em uma granja de suínos de pequeno porte. Para um cenário de 10 anos, os resultados dos indicadores econômicos VPL R$ 57.598,95, TIR 48,38%, Payback Simples 2,06 anos e Payback Descontado 2,3 anos evidenciaram um panorama favorável à utilização dessa tecnologia, com possibilidades de gerar benefícios econômicos, sociais e ambientais.
Economic feasibility of the use of biogas produced from swine culture in replacement to external sources of energy
Keywords: Biodigester; Sustainability; Alternative energy; Biodigestor; Sustentabilidade; Energia alternativa